2001
DOI: 10.14411/fp.2001.041
|View full text |Cite
|
Sign up to set email alerts
|

Experimental infection of immunocompetent and immunodeficient mice with Encephalitozoon cuniculi

Abstract: Abstract. An experimental infection with the microsporidian Encephalitozoon cuniculi Levaditi, Nicolau et Schoen, 1923 was studied using a model of immunocompetent BALB/c mice and immunodeficient SCID mice. The course of infection after intraperitoneal inoculation of E. cuniculi spores was evaluated using the presence of spores in peritoneal macrophages as a criterion. First significant decrease in the proportion of infected cells was recorded on day 9 post infection (p.i.) in BALB/c mice. From day 14 p.i. no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 18 publications
(13 reference statements)
1
2
0
2
Order By: Relevance
“…The results of the present study confirmed the hypothesis concerning variations in pathology and albendazole resistance of different genotypes of Encephalitozoon that had previously been suggested (11,12,39,40). Although there was a disappearance of E. cuniculi genotype III from many organs during the next several weeks after 20 mg albendazole treatment, the number of positive-testing organs seen in the chronic stage of infection was much higher than that seen under conditions of chronic infection caused by E. cuniculi genotype II after treatment with 0.2 mg, mainly in C57BL/6 mice and derived knockouts (10,12).…”
Section: Discussionsupporting
confidence: 91%
“…The results of the present study confirmed the hypothesis concerning variations in pathology and albendazole resistance of different genotypes of Encephalitozoon that had previously been suggested (11,12,39,40). Although there was a disappearance of E. cuniculi genotype III from many organs during the next several weeks after 20 mg albendazole treatment, the number of positive-testing organs seen in the chronic stage of infection was much higher than that seen under conditions of chronic infection caused by E. cuniculi genotype II after treatment with 0.2 mg, mainly in C57BL/6 mice and derived knockouts (10,12).…”
Section: Discussionsupporting
confidence: 91%
“…Lo anterior indica que los ratones inmunosuprimidos e infectados, a pesar de tener una alteración en la respuesta inmune mediada por LT, fueron capaces de controlar la infección, quizá mediante una respuesta inmune innata que fue eficaz en la eliminación del parásito, como ha sido reportado en otras investigaciones realizadas con E. cuniculi (14,17). Además, la respuesta generada por el tejido linfoide asociado a la mucosa intestinal (placas de Peyer, ganglios linfáticos mesentéricos, lámina propia) puede haber contribuido al control del parásito, a la manera de una respuesta inmune local que puede extenderse por todo el sistema o a otras mucosas.…”
Section: Discussionunclassified
“…Se ha reportado que la inmunidad mediada por linfocitos T (LT) juega un papel importante en la defensa de la infección con microsporidios; algunos autores señalan que la respuesta inmune del hospedero contra estos parásitos es del tipo Th1 con producción de IL-2 e INFγ (8)(9)(10)(11)(12)(13)(14)(15)(16)(17).…”
unclassified
“…14–18 Infections with this parasite trigger humoral and cellular immune responses of the hosts, thereby significantly altering their respective immune parameters. 31,32 Hence, they have the potential to compromise the interpretation of scientific experiments considerably and should be avoided.…”
mentioning
confidence: 99%